Analisis dan Perancangan Sistem Informasi Business-to-Business pada Industri Marmer Kabupaten Tulungagung - Dhena Kamalia Fu'adi; Himawat Aryadita; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The marble industry in Tulungagung is one of the leading industries, besides the tourism and agriculture sectors. Ordering products in SMEs marble industry is divided into 2 types, first is when the supplier/retailer come directly into the industry and second is when SMEs marble industry received an order from a large company in Tulungagung. However, both orders are rare, even some SMEs marble never get an order for 1 month. Suppliers and retailers apparently also have difficulty in finding manufacturers to make products they want quickly. B2B e-commerce as a place to make buying and selling as well as marketing is perceived as the right tool to improve this condition. This research is made as an effort to solve the problem by giving priority to analysis and design of system design. The system is designed with the Code Igniter framework and used the Rational Unified Process (RUP) approach. This research is made by analyzing business process, use case, designing activity diagram, sequence diagram, class diagram, physical data model, and user interface. The result of this research is a better business process, which is 23 hours 40 minutes faster with order accepted condition, made 22 features, 22 use cases with activity diagram and sequence diagram with equal amount, and produce 4 controllers and 3 models on the class diagram. Evaluation results show that the flow on the system has been able to be understood by users, navigation and user interface design is easy to understand with an average is 86% in navigation aspect and 93% in interface aspect, and data on the research has been described in sequence.